An Initial Study Into the Long‐Term Influence of Solar Wind Dynamic Pressure on Jupiter's Thermosphere. Issue 11 (22nd November 2018) - Yates, J. N.; Ray, L. C.; Achilleos, N.
Abstract: Jupiter's thermosphere is ∼700 K hotter than expected if it were heated only by solar extreme ultraviolet radiation. Other, more effective heat sources are therefore necessary to explain the high observed temperatures ≥900 K. It has been suggested that heating resulting from the atmospheric interaction with Jupiter's dynamic magnetosphere could account for the excess heat required. However to date, no numerical models have been successful at reproducing Jupiter's hot thermosphere without invoking essentially ad hoc heating mechanisms. Work presented in Yates et al. (2014, https://doi.org/10.1016/j.pss.2013.11.009 ) emphasized the importance of incorporating time dependence in magnetosphere‐ionosphere‐thermosphere coupling when simulating this aspect of the Jovian system. We extend their model (for a single magnetospheric compression or expansion) to simulate the response of thermospheric heating to multiple shocks and rarefactions in the solar wind for the first time. We employ a configurable magnetosphere model coupled to an azimuthally symmetric general circulation model. We compare the response of thermospheric temperatures to these consecutive magnetospheric reconfigurations over a period of 100 Jovian rotations. We find that the thermal structure of our model thermosphere does not respond significantly to such a prolonged period of magnetospheric reconfigurations. Thermospheric mean temperatures increase by a maximum of ∼15 K throughout our simulation. The high‐latitude and high‐altitude thermosphere is most influenced by magnetospheric reconfigurations. While this simulation shows that magnetospheric reconfigurations can heat the thermosphere, it also shows the need to consider a more realistic representation of the coupled Jovian system as well as alternate sources of heating not dependent on the magnetosphere. Key Points: Long‐term solar wind variation leads to thermospheric heating Heating was not sufficient to explain Jupiter's high thermospheric temperatures Magnetosphere‐ionosphere‐thermosphere models need to be more physically realistic